Multidisciplinary program for obesity treatment: Summary of results with adolescents - doi 10.4025/actascihealthsci.v34i2.8934 - Nelson Nardo Junior; Glauco Barnez Pignatta Cattai; Luzia Jaeger Hintze (Universidade Estadual de Maringá, 2012)
This study aimed to evaluate the effects of a multidisciplinary intervention program on the factors: stage of behavior change (SBC), physical self-description (PSD), blood pressure (BP) and physical fitness in obese adolescents. The study was characterized as quasi-experimental type, with 33 adolescents who were evaluated before and after 16 weeks of intervention. The anthropometric and fitness variables, BP were assessed, and we also applied the Stage of Change instrument and PSDQ (Physical Self-Description Questionnaire), in order to measure the SBC and the PSD, respectively. The statistical analysis involved measures of central tendency and dispersion, and the comparison between the initial and final periods was performed by Student's t-test. The comparison between the periods before and after-intervention presented significant differences (p < 0.05) for almost all variables, except for the hip circumference, waist to hip ratio and pull-ups in the adapted bar. The program promoted effective changes in the fat consumption, and habitual physical activity and PSD of habitual physical activity, body fat and appearance. The results are quite promising and evidence the needto expand programs like this, in order to lead to the behavioral change. In this way, the physical education professional has a decisive role on this process.